2021
DOI: 10.3390/ma14195599
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Mechanical Properties of Modified Asphalt and Mixture Using Graphene Platelets (GnPs)

Abstract: Recently, nanomaterials have attracted attention in the field of pavement construction as modifiers to endure heavy loads and climate changes. In this study, conventional asphalt (bitumen) of penetration grade AC (60/70) was modified with graphene platelets (GnPs) at three different contents: 0.5%, 1.0%, and 1.5% by weight of asphalt content. Kinematic viscosity, softening point, penetration, and dynamic shear rheology tests were performed to evaluate the mechanical properties of modified binder. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Another, the graphite powder improves the bond between the and aggregates. It can fill the initiates with microcracks and slow the propagation of cracking [47]. The fond results are in accord with previous research.…”
Section: Figure 10 Ductility Module In Terms Of Different Percentages...supporting
confidence: 91%
See 1 more Smart Citation
“…Another, the graphite powder improves the bond between the and aggregates. It can fill the initiates with microcracks and slow the propagation of cracking [47]. The fond results are in accord with previous research.…”
Section: Figure 10 Ductility Module In Terms Of Different Percentages...supporting
confidence: 91%
“…The fond results are in accord with previous research. The study by Eisa et al (2021) found that the results showed that the mechanical properties of asphalt concrete increased with the contents of graphite powder [47].…”
Section: Figure 10 Ductility Module In Terms Of Different Percentages...mentioning
confidence: 99%
“…Graphene platelets (GnPs), 0.5%, 1.0%, and 1.5% by weight of asphalt content Asphalt Graphene platelets enhance the mechanical properties of asphalt mixture and its performance. [18] Nano-hydrotalcite SMA…”
Section: Additive Matrix Materials Influence/main Findings Sourcementioning
confidence: 99%
“…New solutions are required. Because of that, research using micro-and nano-additives has been conducted for several years [16][17][18].…”
mentioning
confidence: 99%
“…Another promising category of modifying agents for bitumen is represented by graphene [13,14], able to improve the bitumen stiffness at high temperatures and the deformation recovery [15], as well as to reduce the cost of the entire pavement life cycle [16][17][18].…”
Section: Introductionmentioning
confidence: 99%